Development, characterization and evaluation of the dissolution profile of sulfasalazine suspensions - Mayre Aparecida Borges da Costa; Ana Lucia Vazquez Villa; Rita de Cássia da Silva Ascenção Barros; Eduardo Ricci-Júnior; Elisabete Pereira dos Santos (Universidade de São Paulo, 2015)
This paper reports the development, characterization and in vitrodissolution behavior of sulfasalazine suspensions for treatment of chronic intestinal inflammatory diseases. Three formulations were developed, from powdered sulfasalazine obtained from different suppliers. The sulfasalazine was characterized regarding concentration, Fourier Transform Infrared Spectroscopy (FTIR), Differential Scanning Calorimetry (DSC), X-Ray Diffraction (XRD), particle size distribution, polydispersion and solubility. The suspensions were developed and characterized regarding pH, viscosity, density, particle size, sedimentation volume, concentration and dissolution. The pH values were slightly acidic. The method of preparing the suspensions reduced the particle sizes and made the size distribution more homogeneous. The dissolution studies showed that the sulfasalazine suspensions had low solubility in acidic media, but dissolve quickly, reaching levels of 85%, in neutral media or media containing 0.5% of surfactants such as polysorbate 80. Besides this, the sulfasalazine suspensions were classified as having immediate dissolution because they reached dissolution levels near 100% in 20 minutes.